MANAJEMEN KONFLIK SEBAGAI UPAYA MEMPERTAHANKAN KEUTUHAN RUMAH TANGGA (Studi Kasus di Desa Lempur Tengah Kecamatan Gunung Raya Kabupaten Kerinci) - Rama Dhini Permasari Johar; Hamda Sulfinadia (UIN Imam Bonjol Padang, 2020)
This study discusses about marital conflict of the community in Lempur Tengah, one of village in Gunung Raya district, Kerinci Regency. The type of this research is a field research, with a qualitative approach. The primary data source in this study is the community of Lempur Tengah Village, Gunung Raya District, Kerinci Regency. Secondary data sources consist of books and literature related to conflict management in the household. The data collection technique in this study is to use snowball sampling, while the technical data processing consists of 3 related things namely data reduction, data presentation and conclusion. The results of this research revealed several forms of marital conflict that occurred in the households of the Lempur Tengah Village community, Gunung Raya District, namely: verbal violence, physical violence, defensiveness, and withdrawal from the couple. Among the four forms of conflict verbal abuse is a dominant form of conflict. The causes of marital conflict in Lempur Tengah Village community are caused by several factors, namely economic factors, children, communication failure, jealousy and religious factors. The cause of the conflict in the households of the Lempur Tengah Village community was dominated by economic factors. Conflict resolution in this study refers to the 5 conflict management styles proposed by Robbins and Judge, namely the style of competition, collaboration, avoidance, accommodation and the style of compromise. The compromise style is the one most in accordance with what the Lempur Tengah Village community does in resolving conflicts that occur in marriage